Acute lymphoblastic leukaemia: a heterogenous disease. Issue 5953 (8th February 1975) - Haegert, D G; Stuart, J; Smith, J L
Abstract : By using several techniques to detect surface markers on T and B lymphocytes, 11 cases of acute lymphoblastic leukaemia (A.L.L.) were studied. In four cases an insignificant number of markers were detected on the lymphoblast populations. In one case a significant number of blasts formed both sheep red blood cell rosettes and Fc rosettes, suggesting a T-cell origin for the neoplastic cells, and in another case the presence of Fc and C3 receptors on the lymphoblast population indicated a B-cell origin. In a further five cases 14-43% of the blasts had detectable surface immunoglobulin. It is concluded that A.L.L. is a heterogeneous disorder, some cases failing to express surface markers and others having either a T-or a B-lymphocyte origin or both.